Vegetative Compatibility Groups of Fusarium oxysporum f.sp. cubense - Apirusht Somrith; Narong Singburaudom; Onuma Piasai (Agriculture and Natural Resources, 2011)
Vegetative compatibility groups (VCGs) of Fusarium oxysporum f.sp. cubense (FOC) were investigated by collecting 117 isolates from banana plantations in 25 provinces in five parts of Thailand and nit mutants were regenerated and identified for each isolate. VCGs were assessed on the basis of heterokaryon formation between nit1 and NitM of different isolates paired on specific nutrient media in complementary tests. The ability of heterokaryon formation among isolates and VCGs testers was evaluated and the existing physiological races were also discussed. The results indicated that almost 117 isolates of FOC were identified from the Klaui Namwa cultivar and they were classified to 6 VCGs: VCG 0123, VCG 0124, VCG 0125, VCG 0124/0125, VCG 01218 and VCG 01221. VCG 0123 represented the predominant population of FOC in Thailand with 76.0% of total isolates found in all parts of Thailand. VCG 01221 showed the lowest FOC population with 1.7% of total isolates. VCG 0124/0125 was classified as a cross compatible group to which some isolates in VCG 0124 and VCG 0125 were closely related and divided into subgroups. On the basis of pathogenic ability on banana genomics, the FOC race in Thailand was classified to be race 2 and it was less virulent than others worldwide. In this study, the FOC population of Thailand was the primative population and exhibited specific pathogens on one cultivar of banana—namely, Klaui Namwa (ABB genome).